Development of Innovative Teaching Materials with QR Code Assistance for Basic Science Concepts to Enhance Critical Thinking Skills - Nurwahidah; Suranti, Ni Made Yeni; Alimuddin, Nurkhaerat; Ibrahim (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2024)
This study aims to develop innovative teaching materials for the Basic Concepts of Science using QR Codes to enhance the critical thinking skills of prospective elementary school teachers. The study employs the 4D development model, which includes the stages of define, design, develop, and disseminate. The developed teaching materials are integrated with QR Codes, allowing prospective teachers to easily access additional learning resources, rich information, instructional videos, interactive multimedia, and even virtual simulations. The teaching materials are also designed to include learning activities that facilitate the development of critical thinking skills related to the basic concepts of science. The validity testing phase was conducted by five experts, and the validation results were analyzed using Aiken's V to determine the validity index of the developed materials. Based on the data analysis, the teaching materials were found to be valid and suitable for use. The innovative QR Code-assisted teaching materials for Basic Concepts of Elementary Science can effectively train the critical thinking skills of prospective elementary school teachers.